Revisiting the Existing Grading Systems of Glenohumeral Joint Arthropathy and Proposing a Modified Classification - Mishra, Abhishek Kumar; Kushwaha, Sudhir; Charmode, Sundip Hemant; Chauhan, Vishwa (Journal of Surgical Specialties and Rural Practice, 2024)
Abstract Osteoarthritis (OA) of the glenohumeral joint may affect up to 20% of the elderly population. The glenohumeral joint OA is classified in several ways based on different criteria. The notable ones include the Samilson and Prieto classification, Modified Samilson and Prieto classification by Allain, Modified Samilson and Prieto classification by Gerber, Guyette classification, and Kellgren and Lawrence classification. Through this letter, the authors wish to bring it to esteemed editors that a more comprehensive radiological classification is needed to study and categorize the patient and to predict the severity of glenohumeral arthritis. We suggest that X-ray views in anatomical position as well as 45° external rotation and 45° internal rotation will be best suited to plain radiographic classification, which is needed to classify glenohumeral arthritis.